Pengembangan digitalisasi bahan ajar tematik berbasis pendidikan karakter pada siswa kelas VI sekolah dasar - Fajariyani, Fajariyani; Rochmiyati, Siti; Khosiyono, Banun Havifah Cahyo (Tuladha : Jurnal Pendidikan Dasar, 2023)
The objectives of this research are (1) to describe the need for thematic digital teaching materials based on character education, (2) to describe the results of the validity of lesson plan products and digital teaching materials by expert judgment and stakeholders, (3) to describe the results of effectiveness tests of thematic digital teaching materials based on character education . This research is qualitative and quantitative research using the development method or Research and Development (R&D). The instruments used were interviews, observation and document analysis. The research subjects were sixth grade students at SD Negeri Kemadang Tanjungsari, SD Negeri Rejosari Tanjungsari, and SD Muhammadiyah Kemadang Tanjungsari. This research methodology is based on the Borg & Gall development model (simplification of Sukmadinata). The development procedure used in this research consists of 3 stages, namely: (1) preliminary study, (2) model development, and (3) model testing. The results of this research are (1) Based on the results of interviews with students and teachers, observations and document analysis, it shows that digital teaching materials are really needed for effective and interesting learning (2) it produces 2 products, namely lesson plans and thematic teaching materials based on character education which have been validated by 1 expert judgment person and 2 stakeholders. (3) The final product of digital teaching materials is declared suitable for use.